THE INFLUENCE OF CAPITAL STRUCTURE, SIZE, PROFITABILITY, AND DIVIDEND PER SHARE TO COMPANY VALUE WITHIN GROWTH OPPORTUNITY AS MEDIATOR VARIABLE IN INDONESIA STOCK EXCHANGE - desy harfiani harfiani (Equator Journal of Management and Entrepreneurship (EJME), 2021)
This study examines and analyze influence of capital structure, size, profitability, and dividend per share to company value within growth opportunity as mediator variable. This research used secondary data. The data analysis method used in this research is pooled data regression by seeing 30 company in Indonesia Stock Exchange in the year 2016-2019. The result of this study show that the variable capital structure has a positive influence and no significant to company value. Variable size has a negative influence and no significant to company value. Variable profitability has a positive influence and no significant to company value. Variable dividend per share has a negative influence and no significant to company value. And growth opportunity has a negative and no significant to company value. Whereas, capital structure, size, profitability and dividend per share not has significant influence to growth opportunity.